Multilingualism language policy in the EU today: A paradigm shift in language education - Bessie Dendrinos (Peoples' Friendship University of Russia (RUDN University), 2018)
The official rhetoric of the European Union (EU) describes the linguistic diversity by which it is characterised as 'an asset for Europe and a shared commitment', while it also represents languages as commodities for employability, mobility and economic growth. In the context of the EU embracing institutional multilingualism, promoting foreign language learning and suggesting ways of coping with the 'new' multilingual and multicultural classrooms, the management of its complex linguistic diversity is no simple matter. While its language policies reflect consistent efforts to cope with its unique multilingualism, they are often contradictory partly because they are not part of a cohesive overall strategic plan. This paper attempts a review of the EU's commitment to institutional multilingualism, through policies, decisions, recommendations and actions aiming at the management of its multilingualism, focuses on language education policy in particular, and concludes by suggesting that a new didactic paradigm for language education is needed in Europe and beyond because in today's interconnected world, the ability to speak multiple languages and communicate across linguistic divides are critical competences.